INTERNALIZATION OF NATIONAL VALUES IN INDONESIAN LANGUAGE TEXTBOOK CLASS VII JUNIOR HIGH SCHOOL REVISION 2017 - Bella Berliana; Diah Rahma Cahya Agustyowati; Edwin Sanditama; Risti Luluk Nur Afidah (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2022)
Textbooks are mandatory reference materials used in schools. As a reference, textbooks play a role as a medium for shaping students' personalities, which can be done by entering national values in each subject matter contained in the textbook. This study aims to determine the national valuescontained in the Buku Teks Bahasa Indonesia SMP Kelas VII Edisi Revisi 2017. The method used in this research is content analysis research with a qualitative approach. The results of the content analysis in the textbook show national values which include: 1) mutual cooperation, 2) piety to God, 3) humanity, 4) unity, 5) deliberation for consensus, 6) justice, 7) tolerance, and 8) awareness of place to live (love of the motherland). Based on the results of the analysis, it shows that there are complete national valuesin in the Buku Teks Bahasa Indonesia SMP Kelas VII Edisi Revisi 2017.